2005
DOI: 10.1161/01.cir.0000163550.70487.0b
|View full text |Cite
|
Sign up to set email alerts
|

Rise in Insulin Resistance Is Associated With Escalated Telomere Attrition

Abstract: Background-Insulin resistance predisposes to cardiovascular disease and shortens human lifespan. We therefore tested the hypothesis that a rise in insulin resistance in concert with gain in body mass is associated with accelerated white blood cell telomere attrition. Methods and Results-We measured white blood cell telomere dynamics and age-related changes in insulin resistance and body mass index in young adults of the Bogalusa Heart Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
238
6
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(272 citation statements)
references
References 38 publications
15
238
6
13
Order By: Relevance
“…We also have found that the prenatally stressed individuals in this cohort exhibited insulin and leptin resistance, as well as a higher BMI (31). As insulin resistance is associated with chronological age, and longstanding insulin resistance can accelerate biological aging (58)(59)(60), it is possible that insulin resistance also may have contributed to more rapid cellular aging in the PSG individuals. Notably, we have described in this cohort alterations in the regulation of the hypothalamic-pituitaryadrenal axis in the PSG individuals (34).…”
Section: Discussionsupporting
confidence: 52%
“…We also have found that the prenatally stressed individuals in this cohort exhibited insulin and leptin resistance, as well as a higher BMI (31). As insulin resistance is associated with chronological age, and longstanding insulin resistance can accelerate biological aging (58)(59)(60), it is possible that insulin resistance also may have contributed to more rapid cellular aging in the PSG individuals. Notably, we have described in this cohort alterations in the regulation of the hypothalamic-pituitaryadrenal axis in the PSG individuals (34).…”
Section: Discussionsupporting
confidence: 52%
“…Though highly variable, it is heritable [1][2][3][4][5][6] and longer in women than men [1,3,4,[6][7][8][9]. Environmental factors, including smoking [3,10], obesity [9][10][11], psychological stress [12] and low socio-economic status (SES) [13] are ostensibly associated with shortened LTL, underscoring the roles of not only genetic factors but also the environment in fashioning leukocyte telomere dynamics (length and attrition rate). Shortened LTL is also observed in individuals with aging-related diseases, including hypertension [1,7], insulin resistance [11,14,15], atherosclerosis [16,17], myocardial infarction [16,18,19], stroke [9] and dementia [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Critically short telomeres may trigger replicative senescence, albeit other processes, including the capped/ uncapped telomeric status and telomerase activity, are major determinants in this phenomenon. Thus, TL largely registers the replicative history, the cumulative oxidative burden, and, in part, the proliferative potential of somatic cells in culture [87]. The experiments show that the rate of telomere shortening in vitro is modulated by oxidative stress as well as by differences in antioxidative defense capacity between cell strains [88].…”
Section: Clinical Disorders Associated With Age-dependent Telomere Lomentioning
confidence: 91%
“…Shorter TL in leukocytes has been associated cross-sectionally with CVD and its risk factors, including pulse pressure and vascular aging [1,86,[95][96][97], obesity [87,98,99], vascular dementia [88,100], diabetes [98,[101][102][103][104], coronary artery disease (CAD) [1,105,106], myocardial infarction (MI) [107] although not in all studies [108], and cellular turnover and exposure to oxidative and inflammatory damage in chronic obstructive pulmonary disease (COPD) [109]. Leukocyte TL correlates with a subset of measures of cognitive performance, suggesting that it might be a biomarker of cognitive aging in women before the onset of dementia [110].…”
Section: Clinical Disorders Associated With Age-dependent Telomere Lomentioning
confidence: 99%